Contrast between continental and oceanic thunderstorms in producing red sprites and halos - Lu, Gaopeng; Peng, Kang-Ming; Xian, Tao; Wang, Yongping; Ren, Huan; Tian, Ye; Zhang, Mao; Lucena, Frankie; Zhang, Xiaoyang; Huang, Xin; Cheng, Zhengwei (Frontiers in Earth Science, 2022)
The observations of transient luminous events from space-borne platform extend our exploration on the mysteries of sprite phenomenology from continental thunderstorms to oceanic thunderstorms. By combining with ground-based measurements of causative strokes for hundreds of red sprites observed by the Imager of Sprites and Upper Atmospheric Lightnings (ISUAL) during 2004–2016, there is a consensus that negative cloud-to-ground (CG) strokes spawned by oceanic thunderstorms are more readily to produce sprites. The existing ground-based observations in both Caribbean Sea and near the coast of South China, mainly due to the contributions from numerous amateurs, are generally consistent with the implications of ISUAL observations. However, the physical mechanisms that might cause the enhancement of negative CG strength in the ocean remain not completely understood. There have been analyses on several cases of oceanic thunderstorms abundant in producing negative sprites. It seems that the production of negative sprites heavily depends on the size of parent thunderstorms, and they are often generated by thunderstorm conditions that are also favorable for gigantic jets.